IDENTIFYING STRATEGIES TO MINIMIZE INTERGENERATIONAL CONFLICT IN WORKPLACE - Jemima, Rasolofomanana Tahiry Nantenain; Kusumadmo, E. (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2019)
This study was conducted to identify strategies to minimize intergenerational conflict in workplace in an e-commerce company in Madagascar. This company is made up of three generations of people who is different in many ways that often lead conflict in workplace.In this study, 125 out of 150 questionnaires were returned to the researcher to be analyzed and interviews were conducted with four people. The data were analyzed by using NVivo 8.The finding of this study indicates that to minimize intergenerational conflicts: managers should have more understanding on what their employee’s needs and expectations; they must familiarize themselves with them. Establishing internal communication that value everyone is a must to solve intergenerational concern. Training is useful to strengthen team cohesion and mentorship is to break through barriers by encouraging employees of different generations to connect each other and setting compromise improve collaborations level among employees.Keywords: conflict management, intergenerational conflict, multigenerational workplace.